Study on spontaneous combustion characteristics of residual coal in adjacent goaf during mining of small coal pillar working face - Zhenping SUN; Xiao LIU; Tao PAN (Meikuang Anquan)
To recover coal resources as much as possible, the working face of small coal pillars has been gradually increased. However, the small coal pillar will cause the compression and air leakage, which may have an adverse effect on the fire prevention of the working face. This study takes 131103 working face of Liuzhuang Coal Mine as the research object, and studies the influence of small and medium-sized coal pillars on the goaf of the adjacent 131101 working face. The temperature and gas volume fraction of adjacent goaf are monitored by four small coal pillar holes combined with closed wall observation holes. Through the method of releasing SF6 tracer gas through the reserved pipeline in the return air tunnel, the air leakage characteristics of small coalpillar to adjacent goaf are studied. The results show that the large-range compression time of small coal pillar is mainly in the roof periodic weighting period, the key area of air leakage is 20 m miles behind the support; the advance influence range of air leakage of small coal pillar is about 135 m, and this part of coal can effectively prevent coal spontaneous combustion by installing temperature sensors or gas monitoring in advance.